Makna Riwayat Hidup Buddha Gotama bagi Siswa Sekolah Minggu Buddha di Cetiya Kusala Cetana Tegal Angus - Desya Chandra (Jurnal Ilmiah Kampus: Sati Sampajanna, 2022)
The problem raised in this study was to determine the level of studentunderstanding of the meaning of the life history of Buddha Gotama. Thepurpose of this study was to determine the extent of students' understanding ofthe meaning of the life history of Buddha Gotama.This research uses descriptive qualitative method. The subjects of thisstudy were Buddhist Sunday School students and administrators of BuddhistSunday School in Cetiya Kusala Cetana. This research was conducted fromFebruary to May 2020. Data collection techniques used were in the form ofobservations, interviews, and documentation. Data validity tests includecredibility, transferability, dependability, and confirmability. The data obtainedwere analyzed using the Miles and Huberman models, namely data collection,reduction, display, and conclusion drawing.The results of this study are: 1.) Most Cetiya Kusala Cetana Tegal AngusBuddhist Sunday School students have understood the meaning of the story ofGotama's Buddhist Life. Namely: a) Tells the part of the story like, b) Tells a whocharacter introduces the story of the life history of Buddha Gotama, c) Valuesset by students. 2.) Students feel the positive impact after knowing the meaningof the life story of Gotama Buddha. The students have Mettā feelings. Thestudents' faith in Buddha, Dharma and Sangha became very strong. The lives ofstudents are better.